Uncertainty management in production planning process paintedcCab: A case study of truck assembly factory - Achawaporn, Nopphasorn; Chutima, Parames (Asia-Pacific Journal of Science and Technology, 2017)
Nowadays, the management of painted cab’s truck production needs flexibility to support the uncertainty of the production such as color of cab, type of painted cab and the amount painted cab, etc. The case study factory frequently changes the production plan due to the uncertainty of the production, which causes production delay and also increase the production cost, e.g. over time, utility and material costs. Thus, the purpose of this research is to provide a guideline to manage the uncertainty of painted cab schedule management, to be more certain by using the method that improve the control of manufacturing areas. The method applies a heuristic approach such as Shortest Processing Time: SPT associates with the arrangement workstations. In addition, we also improve the arrangement of the purchasing order to make it more appropriate with the working environment. The result shows that the production planning process is improved to be more certain and the duration of the painted cab production is also reduced. Moreover, this research can be applied as a guideline model to alleviate production uncertainties in other products in the future.